Challenges of open data in aquatic sciences: issues faced by data users and data providers - Mesman, Jorrit P.; Barbosa, Carolina C.; Lewis, Abigail S. L.; Olsson, Freya; Calhoun-Grosch, Stacy; Grossart, Hans-Peter; Ladwig, Robert; La Fuente, R. Sofia; Münzner, Karla; Nkwalale, Lipa G. T.; Pilla, Rachel M.; Suresh, Keerthana; et al. (Frontiers in Environmental Science, 2024)
Free use and redistribution of data (i.e., Open Data) increases the reproducibility, transparency, and pace of aquatic sciences research. However, barriers to both data users and data providers may limit the adoption of Open Data practices. Here, we describe common Open Data challenges faced by data users and data providers within the aquatic sciences community (i.e., oceanography, limnology, hydrology, and others). These challenges were synthesized from literature, authors’ experiences, and a broad survey of 174 data users and data providers across academia, government agencies, industry, and other sectors. Through this work, we identified seven main challenges: 1) metadata shortcomings, 2) variable data quality and reusability, 3) open data inaccessibility, 4) lack of standardization, 5) authorship and acknowledgement issues 6) lack of funding, and 7) unequal barriers around the globe. Our key recommendation is to improve resources to advance Open Data practices. This includes dedicated funds for capacity building, hiring and maintaining of skilled personnel, and robust digital infrastructures for preparation, storage, and long-term maintenance of Open Data. Further, to incentivize data sharing we reinforce the need for standardized best practices to handle data acknowledgement and citations for both data users and data providers. We also highlight and discuss regional disparities in resources and research practices within a global perspective.